Essential oils of Lavandula stoechas subsp. luisieri as antifungal agent against fungi from strawberry tree fruit - Domingues, Joana (2021)
Essential oils of Lavandula stoechas subsp. luisieri as antifungal agent against fungi from strawberry tree fruit